Sistem Penunjang Keputusan Rekomendasi Pemilihan Baja Ringan Menggunakan Metode Weighted Product (WP) - Auditya, Yonathan; Akbar, Mutaqin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The use of light steel in building construction has increased significantly in recent years. Due to its advantages, such as high strength, corrosion resistance, and ease of installation and maintenance. However, the complexity of various types of light steel makes it difficult for ordinary consumers to choose, and even risks falling victim to fraud related to quality, price, weight, and A-Z level. Therefore, an effective decision support system is needed to help determine the quality of light steel according to their desired specifications. This research develops a decision support system using the Weighted Product method, which identifies the best light steel alternative based on the criteria of quality, price, weight, and A-Z level. The data sample used includes five light steel alternatives, namely BUKIT, GECO, SMS, TARIGAN, and TASO. The results of the application of this method show that the light steel type “GECO” was selected as the best alternative with a value of 0.341, making it the main recommendation in this study. With this system, it is hoped that users who are still unfamiliar with the world of the construction industry can make better and more precise decisions in the selection of light steel, there by reducing the risk of errors and potential fraud in the process of selecting light steel.